From work motivation to innovative behavior of employees in enterprises - Nguyen, Huy Cong; Tran, Quang Bach; Nguyen, Thi Minh Phuong; Bui, Dinh Viet Hoang; Nguyen, Quoc Khai; To, Xuan Dan; Vu, Thi The (Edelweiss Applied Science and Technology, 2025)
To ensure the survival and development of organizations in a dynamic and competitive environment, managers must seek new approaches to business management (AlEssa & Durugbo, 2021). This study aims to examine the impact of work motivation on employees’ innovative behavior in Vietnamese enterprises through the mediating factors of psychological capital and transformational leadership style in the context of digital transformation. A quantitative research method was employed using structural equation modeling (SEM) analysis. Research data were collected through a survey of 476 employees working in enterprises that have implemented or are in the process of implementing digital transformation, including both state-owned and private enterprises. The findings indicate that work motivation not only has a direct and positive impact but also an indirect impact on employees’ innovative behavior through the mediating factors of psychological capital and transformational leadership style. Additionally, the transformational leadership style was found to impact employees’ psychological capital. These findings provide significant contributions to the literature. Based on these results, the study proposes several recommendations to enhance employees’ innovative behavior in enterprises within the digital transformation context. This study is a useful reference for firms.